2019
DOI: 10.1111/hsc.12846
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the impact of social network change: Experiences of older adults ageing in place

Abstract: Social networks are sources of support and contribute to the well‐being of older adults who are ageing in place. As social networks change, especially when accompanied by health decline, older adults’ sources of support change and their well‐being is challenged. Previous studies predominantly used quantitative measures to examine how older adults’ social networks change. Alternatively, this study explores the impact of changing social networks on older adults’ lives by examining their personal experiences. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Death of a spouse decreased the preference for ageing in place. Neither the existing advice nor hotline telephone services had any impact on this, which suggests the need for community care services aimed at enlarging a bereaved person's social network and providing support in times of distress (Vos et al., 2020). Women had a lower preference to age in place than men, presumably because they are responsible for all domestic chores, which may make them incline towards institutional care as a source of respite; which suggests the need for home help services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Death of a spouse decreased the preference for ageing in place. Neither the existing advice nor hotline telephone services had any impact on this, which suggests the need for community care services aimed at enlarging a bereaved person's social network and providing support in times of distress (Vos et al., 2020). Women had a lower preference to age in place than men, presumably because they are responsible for all domestic chores, which may make them incline towards institutional care as a source of respite; which suggests the need for home help services.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that day‐care services for housebound older people reduce admissions to institutional care (Beswick et al., 2008). Home care nurses can provide supports to older people in periods of distress, and prevent them from entering institutional care (Vos, van Boekel, Janssen, Leenders, & Luijkx, 2020). Day services can be effective in improving activities of daily living (ADL) and instrumental activities of daily living (IADL), but are ineffective in improving functional and psychosocial status (Kono et al., 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to be able to improve PCC by conducting scientific research and achieving its translation to care practice, it is essential to understand the perspectives of older adults. In our research, we always study the perspective of older adults on a specific topic, such as access to long-term care [26,35], technology acceptance [36][37][38][39][40], love, intimacy and sexuality [31,32], and social needs and networks [41][42][43][44]. Although physical or cognitive limitations-including dementia-may complicate this, we showed that it is possible and worthwhile [45].…”
Section: Perspective Of Older Adultsmentioning
confidence: 96%
“…Some studies have considered the nature and qualities of the relationships in a network, mostly aimed at the relationship of the older person with other network participants (14)(15)(16). Looking at the patterns of interaction in the total network relationships could be helpful to improve the support generated by the network.…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of different network constellations makes it possible to identify strengths and weaknesses in informal support and to see which network types are more likely to request formal help than others (5,11,13). Some studies have considered the nature and qualities of the relationships in a network, mostly aimed at the relationship of the older person with other network participants (14)(15)(16). Looking at the patterns of interaction in the total network relationships could be helpful to improve the support generated by the network.…”
Section: Introductionmentioning
confidence: 99%